2015
DOI: 10.15376/biores.10.2.2797-2808
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bamboo after Ionic Liquid-H2O Pretreatment for the Pyrolysis Process

Abstract: Bamboo (Phyllostachys edulis) samples pretreated with ionic liquid (ILs)-H2O mixtures were studied concerning their application in the pyrolysis process.[Bmim]Cl-H2O, [Bmim]BF4-H2O, [Bmim]HSO4-H2O, and [Bmim]Ac-H2O mixture systems were used in the pretreatment process. The characteristics of pretreated bamboo were analyzed, as was cellulose extracted from ILs-H2O pretreated bamboo. The enrichment of cellulose (α-cellulose) in pretreated bamboo was achieved. The amount of char resulting from the pyrolysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…For the jute stick, the yield of solid residue was found to be approximately 14%. In addition, similar results were observed during the pyrolysis process of the other different biomass products [21,[34][35][36][37].…”
Section: Thermogravimetric Analysis Of Jute Sticksupporting
confidence: 79%
“…For the jute stick, the yield of solid residue was found to be approximately 14%. In addition, similar results were observed during the pyrolysis process of the other different biomass products [21,[34][35][36][37].…”
Section: Thermogravimetric Analysis Of Jute Sticksupporting
confidence: 79%
“…Being abundant throughout the whole country, bamboo can be treated as a source of income. Its leaf is claimed to have medicinal benefits among traditional practitioners 2 . Bamboo leaves, also known as Lophaterum, and bamboo shavings are commonly used as relievers for stomach aches, cooling effects and also help to counter the negative flow of qi 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al . reported that hemicellulose component of bamboo treated with BMIM[BF 4 ] at 100 °C reduced whereas cellulose content was increased . However, no information was given about the formation of fibrillation.…”
Section: Introductionmentioning
confidence: 99%